Novel microfluidic graphene oxide–protein amperometric biosensor for detecting sulfur compounds. (8th February 2019) - Ghaemi, Amirhossein; Abdi, Kaveh; Javadi, Shohreh; Shehneh, Masoud Zare; Yazdian, Fatemeh; Omidi, Meisam; Rashedi, Hamid; Haghiralsadat, Bibi Fatemeh; Asayeshnaeini, Omid
Abstract: Sulfur compounds are essential for many industries and organisms; however, they cause serious respiratory problems in human beings. Therefore, determination of sulfur concentration is of paramount importance. The research approach in the field of detecting contaminants has led to smaller systems that provide faster and more effective ways for diagnosis purposes. In this study, a novel portable amperometric graphene oxide–protein biosensor platform is investigated. The main characteristic of this structure is the implementation of a microfluidic configuration. With albumin metalloprotein as the biorecognition element, graphene oxide was synthesized and characterized by transmission electron microscopy and Fourier‐transform infrared spectroscopy (FTIR). Albumin protein was stabilized on the surface of graphene oxide by the application of the N‐(3‐dimethylamionpropyl)‐N‐ethylcarbodiimide hydrochloride/N‐hydroxysuccinimide method. The stabilization was confirmed by FTIR and electrochemistry analyses. The calibration curve of sulfur concentration was determined. When the graphene oxide–protein complex was stabilized by nephion on the surface of the microfluidic system, the response time reduced to 50 Sec, which is a relatively faster response among the similar studies and validated the significant effect of the microfluidic system. The nanosystem had an optimized pH of 7.4 and exhibited high sensitivity in determining sulfide. The results confirm that the portable graphene oxide–protein nanosystem has a fast and accurate response in detecting sulfide.